EXERCISE- AND DEHYDRATION-ASSOCIATED RHABDOMYOLYSIS: PATHOPHYSIOLOGY, CLINICAL FEATURES, MANAGEMENT, AND PEDIATRIC CONSIDERATIONS - Bryam Esteban Coello García; Laura Cristina Silgado Castillo; Byron Estuardo Ávila Sanmartín (EPRA International Journal of Multidisciplinary Research (IJMR), 2026)
Introduction: Rhabdomyolysis is a clinical syndrome characterized by skeletal muscle breakdown with subsequent release of intracellular components, including myoglobin and creatine kinase, into the circulation. Strenuous physical exercise associated with dehydration represents an important trigger and may lead to severe complications such as acute kidney injury. Objective: To review current evidence on rhabdomyolysis and its association with physical exercise, dehydration, and related clinical complications, including considerations in pediatric populations. Methodology: A narrative literature review was conducted using PubMed, Cochrane Library, and Google Scholar databases. A total of 32 relevant articles published in English, Spanish, and Portuguese were selected based on relevance, methodological quality, and clinical applicability. The analyzed literature addressed pathophysiological, clinical, diagnostic, therapeutic, and preventive aspects of rhabdomyolysis associated with strenuous physical exercise, dehydration, and pediatric considerations. Results: The review demonstrated a consistent association between strenuous physical exercise, dehydration, and the development of rhabdomyolysis, characterized by significant elevations in creatine phosphokinase levels and an increased risk of acute kidney injury. Hypovolemia and reduced renal perfusion were identified as key factors influencing clinical severity. Pediatric data also indicate that children and adolescents are susceptible to rhabdomyolysis, particularly in the presence of dehydration and intense physical activity, with early recognition and adequate hydration being essential to prevent complications. Conclusions: Exercise-induced rhabdomyolysis is significantly exacerbated by dehydration, increasing muscle damage and the risk of renal complications. Early recognition, adequate hydration, and preventive strategies remain essential to reduce morbidity and improve clinical outcomes in both adult and pediatric populations.